Acoustic analysis on English oral vowels produced by Acehnese speakers from Aceh Besar by using PRAAT software - Ika Apriani Fata; Ikhwani Ikhwani; Fajar Fitrian; Teuku Mohammad Aulia; Yunisrina Qismullah Yusuf (Proceedings of AICS - Social Sciences, 2017)
This research intends to acoustically analyze English oral vowels produced by the female and male speakers of English teacher candidates in Indonesia, specifically from Aceh Besar. Previous studies have focused on the production of English vowels produced by the Malaysians, Thais, Singaporeans, and the Philippines, among others, but no research has focused on the Indonesian speakers. Hence, this study intends to fill in this research gap. Purposive sampling was used to select five female and five male participants with age ranging from 18-22 years old and born, raised and live in Aceh Besar. Data were recorded in the phonetics laboratory at Syiah Kuala University. The vowels were collected through elicitations of English words which contained the target vowels articulated in carrier sentences. The wordlist is adapted from Pillai, Manueli and Dumanig (2010). The recordings were saved in WAV files, and Praat software version 6.0.14 (Boersma Weenink, 2016) was used to analyze the vowel qualities. The results showed approximate measurements of the English vowels produced by Indonesians who reside in Aceh, by both male and female speakers. The results are expected to become starting points for future related research in the production of English vowels by Indonesian speakers (i.e. English vowel contrasts between native speakers of English and Indonesians, varieties of English, Indonesian English, etc.).